The Changing Scenario of Mathematics Formative Assessment in the Era of Globalization - Ambrosio, Joezel; Bautista, Rhona Lyn; Cabillan, Maria Linda; De Vera, Nora; Unson, John Carlo; Winnan, Glory Ann Julien (International Journal of Scientific Research and Management (IJSRM), 2021)
Researches on formative assessment have mentioned its importance in the teaching and learning method. However, there are little to no known researches on formative assessment centered in Mathematics and higher education. This research intends to investigate the awareness and development of formative assessment in undergraduate Mathematics education in a top university in the Philippines, Saint Louis University, currently having more than 30,000 students. Specifically, this research determines the current scenario of formative assessment as it seeks to recognize the adaptation and usage of formative assessment, identify the challenges and opportunities that Mathematics educators face in formative assessment with regards to globalization, and describe the characteristics of the Mathematics educators based on their extent of use of 21st century formative assessment strategies and tools. Furthermore, this descriptive qualitative research attempts to identify the challenges needed to be overcome by the Mathematics sector to satisfy the globalized skills students needed to attain.